CHEMICAL COMPOSITION OF GALACTIC DISK STARS - Mishenina, T. V.; Basak, N. Yu.; Gorbaneva, T. I.; Soubiran, C.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2007)
Abundances of Na, Al, Ca, in the stars of galactic disks are obtained. The separation of thin and stars on cinematic criterion was made early. The behavior of chemical element abundances with metallicity for studied stars was presented.